2020
DOI: 10.1101/2020.03.16.994152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the SARS-CoV-2 Spike in an Early Prefusion Conformation

Abstract: 23Pandemic coronavirus disease 2019 is caused by the emerging severe 24 acute respiratory syndrome coronavirus 2 (SARS-CoV-2), for which there are no 25 efficacious vaccines or therapeutics that are urgently needed. We expressed three 26 versions of spike (S) proteins-receptor binding domain (RBD), S1 subunit and S 27 ectodomain-in insect cells. RBD appears monomer in solutions, whereas S1 and S 28 associate into homotrimer with substantial glycosylation. The three proteins confer 29 excellent antigenicity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 42 publications
(40 reference statements)
3
23
0
Order By: Relevance
“…2G). This finding is consistent with the thermal denaturation profile of wild type S protein purified from High Five TM insect cells, despite the overall structural differences [31].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…2G). This finding is consistent with the thermal denaturation profile of wild type S protein purified from High Five TM insect cells, despite the overall structural differences [31].…”
Section: Discussionsupporting
confidence: 88%
“…2G). This finding is consistent with the thermal denaturation profile of wild type S protein purified from High Five TM insect cells, despite the overall structural differences [46]. Additional work will be required to assign these transitions to specific domains or modules within the full length COVID-19 spike protein.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“… [36] , [37] , [38] . Several studies have shown that the ectodomain and the RBD expression in eukaryotic systems are stable and appear in the monomer conformation in high yield; and that soluble ACE2 binds to both monomer and trimer conformations [37] , [39] , [40] , [41] , [42] . In this context, to fully characterize the S protein, it is important to explore both the monomer and trimer in structural studies.…”
Section: Resultsmentioning
confidence: 99%
“…This structure appeared to be more compact overall, and the model could not accommodate the presence of the SD1 domain. 34 Whether these disparities are the consequence of differences in expression hosts (e.g., glycosylation or other processing functions) or the lack of stabilizing mutations remains an open question, although RBD recognition and antigenicity were preserved.…”
Section: Discussionmentioning
confidence: 99%